Around the world in eighty days - Verne, Jules, 1828-1905 (Penguin classics, 2004)
In 1872 Phileas Fogg wagers that he can circle the earth in eighty days and traveling by steamer, railway, carriage, sledge, and elephant he wins his bet in seventy-nine days, twenty-three hours, and fifty-seven minutes.